2014
DOI: 10.1128/genomea.00002-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Petroleum Hydrocarbon-Degrading Pseudomonas aeruginosa Strain PK6, Isolated from the Saurashtra Region of Gujarat, India

Abstract: Pseudomonas aeruginosa strain PK6, a potential petroleum hydrocarbon-degrading soil bacterium, was isolated from a site contaminated by a petroleum hydrocarbon spill from an automobile service station in Junagadh, Gujarat, India. Here, we provide the 6.04-Mb draft genome sequence of strain PK6, which has genes encoding enzymes for potential and related metabolic pathways of the strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Pseudomonas aeruginosa is a gamma proteobacterium which is known to produce rhamnolipid and able to utilize and grow in high concentrations of crude oil. Rhamnolipid itself has been reported capable of stimulating biodegradation of hydrocarbons (Patel et al 2014).Udochukwu et al (2014 stated that P. aeroginosa is the predominant species in petroleum degradation and always found in every oil pollution site analyzed. Chamkha et al (2011) successfully isolated Klebsiella oxytoca strain BSC5 from an off shore oil field in Tunisia.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a gamma proteobacterium which is known to produce rhamnolipid and able to utilize and grow in high concentrations of crude oil. Rhamnolipid itself has been reported capable of stimulating biodegradation of hydrocarbons (Patel et al 2014).Udochukwu et al (2014 stated that P. aeroginosa is the predominant species in petroleum degradation and always found in every oil pollution site analyzed. Chamkha et al (2011) successfully isolated Klebsiella oxytoca strain BSC5 from an off shore oil field in Tunisia.…”
Section: Resultsmentioning
confidence: 99%
“…If the pesticide is not degraded or detoxified quickly enough, the risk of its off-site migration may pose health risk to humans (Fulekar and Geetha, 2008). The manufacturing and formulation process of chlorpyrifos also generate waste which needs to be treated (Patel et al 2014). Catabolism and detoxification metabolism occur when a soil microorganism uses the pesticide as a carbon and energy source.…”
Section: Introductionmentioning
confidence: 99%
“…It have been reported that Pseudomonas sp possesses genes that code for enzymes such as catechol dioxygenase, alkane 1-monooxygenase and alkane sulfonate monooxygenase [16] that help in the breaking down of hydrocarbon chains.…”
Section: Determination Of Soil Percentage Oxidizible Organic Carbon mentioning
confidence: 99%